2012
DOI: 10.1142/s0219091512500142
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Underinvestment, Overinvestment and CEO's Compensation

Abstract: This research separates out the incentive and entrenchment effects of executive pay and uses it to test if the agency cost is that of underinvestment or overinvestment. I find that investments increase with dollar value of stock and options owned by the CEO but decrease with percentage of shares owned by the CEO. These results are robust to alternate measures of investments such as R&D, acquisitions, and change in assets. It appears that the positive relationship between investment and percentage of stocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…Studies examining the effect of compensation on managers' decision and behavior still show a mixed result. Some researchers provided evidences of the alignment effect of compensation (Lei et al, 2014;Baxamusa, 2012;Broussard, Buchenroth, & Pilotte, 2004), but some others demonstrated an entrenchment effect where compensation actually motivates managers to take action which is not in line with the interests of shareholders (Baxamusa, 2012;Aggarwal & Samwick, 2006). We argue that this mixed result might be due to two reasons, the compensation effect on managerial decision and behavior might be contextual in nature.…”
Section: The Effect Of Compensation and Religiosity On Managers' Csr mentioning
confidence: 72%
See 2 more Smart Citations
“…Studies examining the effect of compensation on managers' decision and behavior still show a mixed result. Some researchers provided evidences of the alignment effect of compensation (Lei et al, 2014;Baxamusa, 2012;Broussard, Buchenroth, & Pilotte, 2004), but some others demonstrated an entrenchment effect where compensation actually motivates managers to take action which is not in line with the interests of shareholders (Baxamusa, 2012;Aggarwal & Samwick, 2006). We argue that this mixed result might be due to two reasons, the compensation effect on managerial decision and behavior might be contextual in nature.…”
Section: The Effect Of Compensation and Religiosity On Managers' Csr mentioning
confidence: 72%
“…First, compensation is one of the most widely used tools to direct managers' decisions and actions to be in line with the interests of shareholders. Compensation is an organizational factor that has been shown to play a role in influencing managers' decisions and behavior (Malmendier & Tate, 2015;Baxamusa, 2012;Malmendier & Tate, 2005a;2005b). Second, we argue that religiosity contains moral or ethical values that is in line with CSR in which moral or ethical values are one of the dimensions.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Additionally, Strobl [36] summarizes the relationship between managerial incentives and investment policy. Furthermore, Baxamusa [37] examined policies to reduce risk or overinvestment in production capacity through incentives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One class of models (Miller 1977;Hong et al 2006;Baxamusa 2012) predict that the diversity of opinion about the future cash flows of the firm lead to decrease in demand for the firm's stocks. The implication for the acquirer is as follows.…”
Section: Relevant Models For Information Asymmetrymentioning
confidence: 99%